2009
DOI: 10.1016/j.ejor.2007.11.033
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic approach for big bucket multi-level production planning problems

Abstract: Multi-level production planning problems in which multiple items compete for the same resources frequently occur in practice, yet remain daunting in their difficulty to solve. In this paper we propose a heuristic framework that can generate high quality feasible solutions quickly for various kinds of lot-sizing problems. In addition, unlike many other heuristics, it generates high quality lower bounds using strong formulations, and its simple scheme allows it to be easily implemented in the Xpress-Mosel modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 36 publications
1
75
2
Order By: Relevance
“…Akartunalı and Miller [2009] proved that the LP relaxations of S-ILS, FL, and SR yield the same lower bound for the CLST-ML problem. To the best of our knowledge, no other theoretical results have been demonstrated on their relationships.…”
Section: Equivalence Of Strong Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Akartunalı and Miller [2009] proved that the LP relaxations of S-ILS, FL, and SR yield the same lower bound for the CLST-ML problem. To the best of our knowledge, no other theoretical results have been demonstrated on their relationships.…”
Section: Equivalence Of Strong Formulationsmentioning
confidence: 99%
“…Denizel et al [2008] subsequently showed the equivalence of the LP relaxations of the FL and SR formulations for the CLST-ML. Akartunalı and Miller [2009] added (l, S) separation cuts to the ILS formulation, and then showed that this strengthened version of the formulation provides the same LP lower bounds as the FL and SR formulations for the CLST-ML. Furthermore, Akartunalı and Miller [2007] compare a wide variety of different lower bounds for the CLST-ML.…”
Section: Introductionmentioning
confidence: 99%
“…For these and other reasons, the polyhedral structure of this model is, in general, rich and complicated. However, solving such small problems to optimality (i.e., solving the pricing problem in our framework) is computationally tractable, as attested by authors who have used such submodels in primal heuristics (e.g., Stadtler 2003, Federgruen et al 2007, Akartunalı and Miller 2009. In this paper, although we do not characterize new families of inequalities, the methodology we develop is capable of providing information concerning how effective such results could be.…”
Section: Introductionmentioning
confidence: 96%
“…Solution approaches for lot-sizing problems have varied from heuristic methods to exact approaches based on mathematical programming. A variety of heuristics can be found in Stadtler (2003), Pochet and Van Vyve (2004), Federgruen et al (2007), and Akartunalı and Miller (2009). Mathematical programming approaches have mainly involved adding valid inequalities (e.g., Barany et al 1984;Constantino 1996;Wolsey 1988, 1994) and extended reformulations of the problem (e.g., Krarup and Bilde 1977, Eppen and Martin 1987, Rardin and Wolsey 1993, although few studies facilitate other techniques, such as Lagrangian relaxation (e.g., Billington et al 1986) and Dantzig-Wolfe decomposition (e.g., Bitran andMatsuo 1986, Degraeve andJans 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Melo and Wolsey (2010) propose a dynamic programming algorithm with an improved running time, O(n 2 log n), and a compact tight extended reformulation for 2-ULS-F. For a review of valid inequalities and extended formulations for m-ULS-F, we refer the reader to Pochet and Wolsey (2006). An effective heuristic for capacitated m-ULS-F using strong formulations for each echelon is proposed in Akartunalı and Miller (2009).…”
Section: Introductionmentioning
confidence: 99%